STRUCTURE AND VALUE DISTRIBUTION IN THE MARKETING CHAIN OF SMALLHOLDER ARABICA COFFEE IN SOUTH TAPANULI REGENCY - Ade Anisa; Rafiqah Amanda Lubis; Mukhlis; Aisyah Nurmi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Smallholder Arabica coffee in South Tapanuli Regency has strong potential as a leading commodity; However, farmers face persistent challenges, including weak bargaining power and unequal value distribution along the marketing chain. This study aims to analyze the structure of the Arabica coffee marketing chain, examine farmers' perceptions of the marketing system, and identify factors influencing farmers' income. The research was conducted from March to April 2025 in Simanosor, within the Darul Mursyid Islamic Boarding School (PDM) area, South Tapanuli Regency. A quantitative descriptive method was applied using purposive sampling of 30 Arabica coffee farmers. Data analysis included descriptive analysis of the marketing chain, Likert scale measurement for farmers' perceptions, and multiple linear regression to determine income-influencing factors. The results indicate that all farmers sell their harvest as red cherries, with an average price of IDR 17,450/kg and an average annual net income of IDR 103,516,667. Farmers' perceptions of the marketing system are categorized as very positive, with an average score of 4.91 out of 5. Regression analysis reveals that selling price and production volume significantly affect farmers' income, while cooperative access and price information access do not. The model's R² value of 0.741 shows that 74.1% of income variation is explained by the variables. These findings highlight the importance of improving productivity and stabilizing farm-gate prices to enhance farmers' income.